The Impact of State Budgets on the Kidney Industry and People with ESRD - Schrag, LMSW, ACSW, Wendy Funk (The Journal of Nephrology Social Work, 2012)
While the economy in the United States is improving, states continue to struggle to balance their budgets. Over the past several years, negative effects of budget reductions have been experienced by people with end-stage renal disease (ESRD) and dialysis providers. This article explores the varied reductions, their impact on people with ESRD and dialysis providers, and describes advocacy efforts. Coalitions are especially valuable in advocating for continued funding of benefits and services related to ESRD.